What is the policy focus for tourism recovery after the outbreak of COVID-19? A co-word analysis - Shao, Yuhong; Hu, Zhongyi; Luo, Mingzhi; Huo, Tingting; Zhao, Qingxue (Current issues in tourism, 2021)
Policies for tourism recovery are highly instrumental in achieving tourism development after the outbreak of COVID-19. To understand these policies, this study performed the co-word analysis to map the topics of 140 recovery policies for tourism in China. Four core themes are identified in these policies, namely (i) prophylactic measures, (ii) tourism recovery and development, (iii) policy support, and (iv) departmental management. Moreover, the focus of policy measures varies by region within China. This study provides insights into further research on health-related crises and crisis recovery management in tourism, especially for developing countries and regions.